The News Coverage of Indonesia Media toward AEC - Heditia Syahputri Damanik (Universitas Jenderal Ahmad Yani, 2016)
The paper aims to elaborate the analysis of news coverage of Indonesia media toward ASEAN Economic Community (AEC) issue. Each media has its own framing of the news. I would like to know the framing of several online media in Indonesia to respond the AEC issue. The paper will discuss the news from two of popular online media in Indonesia. The paper would analyze news using the framing analysis. Through that way, the paper would present the comparison of how media’s framing about AEC. Do the two online media frame AEC as the battle field to gain national interest as realism- mercantilism paradigm point of view or frame AEC as the mutual effort of ASEAN state members to reach the mutual prosperity as regional entity like neo-liberalism paradigm sees it?